(untitled) (Research, Society and Development, 2023)
Introduction: Maternal mortality is a major public health problem in Brazil affecting mainly women with low income and low educational level, and postpartum hemorrhage (PPH) is the main aggravating factor of this factor. PPH is defined as blood loss greater than 500ml of blood vaginally or any loss that causes hemodynamic instability. Objective: To highlight the main causes and behaviors performed by the nursing team in the care of postpartum hemorrhage. Methodology: This is an integrative review of literature produced in the analysis of articles in the Virtual Health Library (VHL) in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), National Library of Medicine of the United States of America (MEDLINE), Nursing Databases (BDENF). Results: After performing an analytical reading, 08 articles were selected because they had themes consistent with the study. Uterine atony was identified as the main cause of postpartum hemorrhage. Conclusion: The nursing team is indispensable in the early identification of maternal complications, especially PPH. It is important to correctly measure the vital signs of the parturient, offer oxytocin after delivery, encourage breastfeeding and skin-to-skin contact when there is no restriction, avoid routine episiotomies in delivery rooms and measure hemoglobin and hematocrit levels of puerperal women.